The new public management in Peru - Arias Mercado, Luis Alberto (2019)
Objective: This article responds to the need to understand the influence of human talent in the management and development of public managers, in its dimensions: components of knowledge, skills and attitudes (know how to be, know know, know how to do). In addition, it is part of the research of the public sector, by exposing the progress of the study of the new management of human talent in Peruvian public organizations. Method: The investigation is of descriptive scope and inductive method, because although it locates the population-sample of study in the managerial officers of the local organization (District Municipality of San Isidro, in Lima-Peru), the common characteristics and / or similar of public organizations in the country, as well as the cognitive elements of human talent. Result: A modern and evolving term of the administration of the personnel that works in the State has been established and has been observed through the modification in the Civil Service Legislation in recent years. In addition, contributions can improve their adaptation and / or adaptation to the conditions of public agencies at the central and regional levels of the country.